Lithium chloride attenuates suppressed differentiation induced by mechanical strain in cementoblasts. (3rd September 2019) - Ge, Mengke; Zhou, Chenchen; Li, Huang; Li, Yuyu; Xu, Yang; Wang, Xin; Zou, Shujuan
ABSTRACT: Aim : The purpose of this study was to investigate the influence of mechanical strain on OCCM-30 cementoblast differentiation and Wnt/β-catenin pathway activity. Materials and Methods : Mechanical tension in the form of 2500-µ strain was applied to the cells using the Forcel four-point bending system, with or without the Wnt signaling activator, lithium chloride. Changes in cell differentiation and the expression of Wnt/β-catenin pathway components in response to strain and lithium chloride were assessed by real-time PCR, immunofluorescence, and western blotting. Results : The mRNA expression levels of the cementoblastogenesis-related genes alkaline phosphatase, runt-related transcription factor 2, and collagen 1, were decreased with mechanical strain. Similarly, the Wnt signaling pathway component genes LRP5, AXIN2, and LEF1 were decreased. The immunofluorescence assay demonstrated that scant β-catenin underwent nuclear translocation after the cells were subjected to mechanical strain. Moreover, western blotting showed that the protein levels of both β-catenin and phosphorylated β-catenin were increased after mechanical strain. In the presence of lithium chloride, the differentiation that was suppressed by mechanical strain was attenuated. Conclusions : 2500-µ strain mechanical strain inhibited cementoblast differentiation activity in vitro, which could be alleviated by actviating Wnt/β-catenin signaling using lithium chloride.